2016
DOI: 10.1186/s12887-016-0741-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for vitamin D insufficiency and deficiency at birth and associated outcome

Abstract: BackgroundOccurrence and consequence of cord blood (CB) vitamin D insufficiency/deficiency has not been adequately explored despite rising concern regarding this topic in pediatrics. This study was designed to determine the rate, maternal risk factors, and clinical outcomes in infants in association with vitamin D insufficient/deficient status at birth.MethodsAmerican Academy of Pediatrics (AAP) defined levels (ng/mL) were utilized to categorize the vitamin D status in CB samples as deficient (5–15), insuffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…The prevalence of 25OHD deficiency (<20 ng/ml) was lower than that reported in infant cord blood in the United States [24] and in a recent French study [25], which showed about two thirds of newborns with 25OHD level <20 ng/ml. This discrepancy may be due to the population selection at inclusion, which thus differed from the targeted population [17] and the follow-up as described, with older mothers, having higher incomes and education and higher 25OHD levels in included than excluded children.…”
Section: We Report Generally Low Serum 25ohd Level At Birth In This Scontrasting
confidence: 60%
“…The prevalence of 25OHD deficiency (<20 ng/ml) was lower than that reported in infant cord blood in the United States [24] and in a recent French study [25], which showed about two thirds of newborns with 25OHD level <20 ng/ml. This discrepancy may be due to the population selection at inclusion, which thus differed from the targeted population [17] and the follow-up as described, with older mothers, having higher incomes and education and higher 25OHD levels in included than excluded children.…”
Section: We Report Generally Low Serum 25ohd Level At Birth In This Scontrasting
confidence: 60%
“…Similar finding was reported in a study done by Marshall et al, who stated that younger maternal age was associated with cord blood vitamin D deficiency or insufficiency. 8 13 mothers were primiparous and 17 were multiparous. The mean vitamin D levels in the primiparous mothers was 13.68±3.5 ng/ml and in the multiparous mothers was 16.27±4.19 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. data (NHANES 2003–2006) showed that 11% of women of childbearing age were deficient in vitamin D, while another 26% were insufficient [Zhao, Ford, Tsai, Li, & Croft, ], using a conservative definition (<12 and 12 to <20 ng/mL, respectively, which combined are defined as deficient in other studies, equivalent to 50 nmol/L). Higher rates of deficiency have been reported in other studies including of pregnant women [Hamilton et al, ; Kiely, Hemmingway, & O'Callaghan, ; Marshall, Mehta, Ayers, Dhumal, & Petrova, ]. “Vitamin D” refers to a group of steroid molecules, with formation of vitamin D 3 , the major circulating form, in the body dependent on sunlight (UVB) exposure.…”
Section: Introductionmentioning
confidence: 97%
“…There is increasing evidence of associations of vitamin D deficiency with a wide range of maternal and child health conditions in addition to the well‐known effect on calcium metabolism and bone mineralization [Basit, ; Dror et al, ; Holick, ; Marshall et al, ]. Vitamin D has been shown to play a role in brain development, leading to the suggestion of a possible association with ASD a decade ago [Cannell, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation